Manejo e monitoramento de impactos sobre o ecossistema em áreas protegidas de cerrado: estrutura da vegetação, gramíneas exóticas e incêndios - Batista, Flávia Regina de Queiroz (2019)
The Cerrado is the richest, perhaps the most threatened savannah in the world, and only 3% of its area is protected by law. These are extremely valuable and strategic areas for the conservation of the Cerrado, but suffer numerous external and internal pressures. Among the main management concerns for the Conservation Units (UC) of the Cerrado are fires and biological invasion. This work investigates how the interference of the management and the dynamics of the fire and the invasion of exotic grasses alter the phytophysiognomies of cerrado, and is divided in chapters that investigate respectively: 1) the difficulties in producing a map of sufficient accuracy to support studies of dynamics of vegetation structure; 2) the effectiveness of the current fire management system and the challenges of integrated fire management in the last two decades; 3) the invasion by exotic grasses and their relation with the topography of the terrain, tracks and roads in and around the study area. Landsat 8 images from a period of 5 years from 2013 were used and calculated for 5 different time intervals - monthly, inter-monthly, annual, yearly, quinquennial - sets of metrics based on 18 indices derived from reflectance values of the bands of these images besides the values of reflectance of the bands, data sampled in the field and semiautomatic classification for the mapping of the vegetation classes of the National Park of Emas (PNE). From a replicable model it was possible to elaborate a map with 89% accuracy and nine classes of phytophysiognomies, reducing the costs and the subjectivity of the manual work of data collection and posterior corrections. Using metrics elaborated from a digital elevation model and data of presence and absence of Urochloa sp on internal tracks and along the edges of the UC. Four models were tested using morphometric parameters, distances to tracks and roads in contrast to the presence or absence of the species. The results point to the importance of anthropic disturbances, terrain topography, and indicate that the force of water in its runoff is very relevant in establishing the species in new areas. In order to understand the spatial and temporal behavior of fire in the Emas National Park (PNE), the frequency of burnings for the different phytophysiognomies was analyzed, the correlation between the number of heat spots and the extent of the scars and the influence of the environmental variables surface, precipitation and accumulation of biomass). The scars of burned areas, heat sources, climatic variables - rainfall and temperature of the earth's surface (°C) - dry biomass surface and accumulated biomass for burned and unburned areas were analyzed. The annual peak of heat sources pointed with great accuracy to the occurrence of burnings in the PNE area, the number of outbreaks showed to be a good indicator of scar occurrence and size, the extent of area with dry biomass at categories 'very high' and 'critical' is a risk indicator of large fires and a reasonable predictor of areas that serve as a blockade to the spread of fires. The current fire management plan through firing and natural burning during the dry season has brought advances in fire prevention, but it is necessary to consider the use of prescribed controlled burns.